The Gateway to Computer Science Excellence
0 votes
1.7k views
by (219 points) | 1.7k views

2 Answers

0 votes
(a+b'+a'b)c'

=(a+b'+a')c'

=(1+b')c'

=c'
by Boss (13.9k points)
0
can u show explaination with kmap? m getting different answer
0

Check out this

+1

Is this correct?

0
yes its correct
0 votes

=[a+(b'+a')(b'+b)]c' distributive law

=[a+(b'+a').1]c' identity 

=[a+a'+b']c' commutative 

=(1+b')c' identity

=c' by theorem x+1=1

by (457 points)
Quick search syntax
tags tag:apple
author user:martin
title title:apple
content content:apple
exclude -tag:apple
force match +apple
views views:100
score score:10
answers answers:2
is accepted isaccepted:true
is closed isclosed:true
50,737 questions
57,336 answers
198,445 comments
105,202 users